A THERMODINAMIC CORROSION STUDY OF CARBON STEELS IN HYDROGEN SULFIDE - EXPLORING CHEMICAL EQUILIBRIUM CONCEPTS - Oliveira, Mariana Cristina de [UNESP]; Lima, Alexandre Pereira de [UNESP]; Figueredo, Rodrigo Monzon [UNESP]; Acciari, Heloisa Andrea [UNESP]; Codaro, Eduardo Norberto [UNESP] (Soc Brasileira Quimica, 2018)
This study addresses an inherent problem to the oil and natural gas exploration and production industry, the corrosion of pipes and tanks by H2S. H2S with water emulsified in the oil or H2S with the water vapor mixed in the gas, they make the acid environment leading to corrosion. This is commonly manifested by the formation of insoluble sulfides on the surface of the carbon steels destined for this purpose. The evolution of the corrosion process depends on the composition and physicochemical characteristics of sulfide film. In this context, we intend to interpret the conditions of formation and precipitation of iron sulfides as a function of pH, using concepts of chemical equilibrium, electrode potential and electrochemical cell that are part of the subjects of chemistry.
Keywords: hydrogen embrittlement; sour corrosion; carbon steels; teaching corrosion